Sexually transmitted infections and HIV knowledge, attitudes, and practices amongst first-year students at a university setting in South Africa (African Journal of Biomedical Research, 2024)
Sexually transmitted infections and HIV are health issues of concern and the issue of STI and HIV is public interest to university students, staff and government. The aim of the study was to determine the knowledge, attitudes and practices amongst first year students at a university setting in South Africa. A quantitative cross-sectional descriptive survey was conducted at a University of Technology in Vanderbijlpark, Gauteng Province, South Africa. A total of 362 students participated in the study resulting in a response rate of 97%. Data were collected by using an anonymous self-administered questionnaire that was adapted from validated questionnaire. Descriptive and inferential statistics were employed for data analysis using Strata mini version 13.0. The significant level of p value was determined at p